Toleransi dan Dialog sebagai Nilai Etika dalam Al-Qur'an - Firmansyah, Firmansyah; Putra, Dayul Seven (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2023)
Tolerance and dialogue as ethical values in the Qur'an are very interesting to study because in social life there is a need for these two elements. The formulation of the problem is broken down into questions, namely a). What is the definition and essence of tolerance, b). What are the limits of tolerance in the Koran, c). What is the relationship between tolerance and dialogue as ethical values in the Koran? This research is included in library research or library research, namely by analyzing themes related to tolerance and dialogue as ethical values in the Koran in order to obtain concrete and reliable data. Tolerance is popularly known as samaha or often called tasamuh which means forgiveness, forgiveness and forgiveness. Tolerance often leads to positive traits, where every human being is given the freedom to choose. For example, in embracing a religion according to one's own beliefs there appears to be an obligation. In the Qur'an there are many verses that talk about tolerance, for example: Q.S. Al-Baqarah: 256, Q.S. AlAn'am: 108, Q.S Yunus: 99, Q.S Al-Mumlahanah: 7-9, Q.S Al-Kafirun: 1-6, then dialogue and tolerance are not the final goal in social life, but a process to continue to the next goal. The involvement of each individual and group in social life is very important. Remembering dialogue and tolerance can take place if individuals and groups can work together and respect each other's differences. In other words, tolerance can be established well by using good dialogue.